Consultation skills of young doctors: II–Most young doctors are bad at giving information. Issue 6535 (14th June 1986) - Maguire, P; Fairbairn, S; Fletcher, C
Abstract : Forty young doctors, half of whom had had feedback training in interviewing as students, were assessed five years later. Each interviewed three patients and after being given results of examination, investigations, and diagnosis and prognosis returned to discuss them with each patient for 10 minutes. These discussions were filmed on videotape and evaluated. There was no difference between the scores of interview trained and control doctors. Though most gave simple information on diagnosis and treatment, few mentioned investigations, aetiology, or prognosis. Very few obtained and took any account of patients' views or expectations of these matters. Some young doctors do discover for themselves how best to give patients information and advice, but most remain extremely incompetent. This is presumably because they get no training as students in this important aspect of clinical practice. This deficiency should be corrected, and competence tested before qualification to practise.